Growth and reproduction of dusky dolphins (Lagenorhynchus obscurus) in Aotearoa New Zealand : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Science (MSc) in Zoology at Massey University, Albany, Aotearoa New Zealand - Poelijoe, Denise (Massey University, 2024)
Dusky dolphins (Lagenorhynchus obscurus) are a semi-pelagic species widely distributed in the southern hemisphere. Our understanding of dusky dolphin life history in New Zealand waters has been limited by the small sample sizes and limited geographic coverage of previous studies. Here, I assess age, growth, allometry and reproductive biology from 138 individuals (51 females, 73 males and 14 unsexed individuals). Data originated from stranding and bycatch events around the Aotearoa New Zealand coast from 1960 to 2023. The total body length of females and males varied between 83 to 195cm (mean = 158.1; SD = 27.6; n = 51), and 87 to 192cm (mean =160.1; SD = 25.8; n = 73), respectively. Morphological measurements of males (n = 55) and females (n = 39) were analysed across 25 external measurements, exhibiting negative, positive, and isometric allometry. No growth differences between sexes were observed. Size and shape dimorphism was analysed across 29 external morphological measurements of physically mature individuals. No sexual size or shape dimorphism was observed in the appendage, girth, or blubber measurements. Significant dimorphism between sexes was observed in the snout to genital slit length. Age was estimated from decalcified thin sections of teeth; maximum ages recorded in males and females were 22 and 14 years, respectively. Physical maturity was estimated from asymptotic length obtained using Gompertz growth models. Males and females were estimated to obtain physical maturity at 171.5 and 170cm, respectively. Reproductive parameters were assessed (n = 39) through gross and histological examination of gonads across in males (n = 22) and females (n = 17). The average length at attainment at sexual maturity for males was 170.4cm. For females, the average length at attainment of sexual maturity was 167.5cm, though a lack of age overlap prevented age at sexual maturity being assessed for either sex. Five foetuses ranged in total body length from 25.5 to 81cm, with the smallest born males and females measuring 91.5 and 102cm, respectively. Length at birth could not be determined due to a lack of overlap between measurements of unborn foetuses and newborn neonates.
Keywords: 310903 Animal developmental and reproductive biology